RDA perceptions among Malaysian catalogers - Mansor, Yushiana; Ramdzan, Emilia (Emerald Group Publishing Limited ., 2014)
Purpose – This study aims to investigate Malaysian catalogers’ awareness, familiarity and understanding of the new bibliographic content standard, i.e. Resource Description and Access (RDA).